Viktor Shklovski, lector del Quijote - Sanmartín Ortí, Pau (Dicenda. Estudios de lengua y literatura españolas, 2008)
During his career as a critic, Viktor Shklovsky practiced a model of literary analysis in which his style is infected by the devices of the writer studied. This kind of critic not only examines the literary work but it continues and extends its devices in the essayistic work. From these perspective, it could be interesting to compare the two Viktor Shklovsky’s readings of the Quixote –O teorii prozy (1925) and Xudoz˘estvennaja proza (1959)– in order to verify what kind of continuity exists between one and other. As it is frequent in Shklovsky’s writings from the thirties, the second reading retracts many of the formalist statements exposed in the first one. Now then, an attentive look discovers behind these kind of denials a clever wielding of Cervantes’ irony, that tries not to commit a betrayal but to maintain a tradition from his past as a formalist critic.